1989
DOI: 10.1164/ajrccm/140.4.955
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nicotine Levels after Inhalation of Aerosolized Nicotine

Abstract: Smokers were given 5 mg of aerosolized nicotine over a 5-min period on 3 separate days to determine if this mode of nicotine delivery could produce nicotine levels similar to those reported from cigarette smoking. Our subjects' mean nicotine level increased from a pretrial level of 12 +/- 2 ng/ml to a peak of 32 +/- 7 ng/ml at 2.5 min after completion of the inhalation. Cough was the most prominent side effect and seemed to be related to irritant effects of the aerosol. Seven of the 16 subjects dropped out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…There are reports of nicotine administration to humans through aerosol inhalation. Their clinical significance has yet to be demonstrated (Burch, Erbland, Gann, & Hiller, 1989;Rose, Turner, Murugesan, Behm, & Laugesen, 2010;Simis et al, 2008). Chronic nicotine administration to rats by aerosol inhalation was suggested in an abstract (Littleton & Umney, 1977), but this study has not resulted in further publication.…”
Section: Discussionmentioning
confidence: 92%
“…There are reports of nicotine administration to humans through aerosol inhalation. Their clinical significance has yet to be demonstrated (Burch, Erbland, Gann, & Hiller, 1989;Rose, Turner, Murugesan, Behm, & Laugesen, 2010;Simis et al, 2008). Chronic nicotine administration to rats by aerosol inhalation was suggested in an abstract (Littleton & Umney, 1977), but this study has not resulted in further publication.…”
Section: Discussionmentioning
confidence: 92%
“…To ameliorate the side effects associated with cessation of smoking, a nicotine aerosol is sometimes used [5,39]. The aerosol administration of nicotine is superior to oral or transcutaneous administration, because it imitates administration via cigarette smoke.…”
mentioning
confidence: 99%
“…Molecular and electrophysiological analyses have documented nicotinic receptor (nAChR) expression by airway sensory nerves (Kuo et al, 1989;Lee et al, 1989;Kuo et al, 1990;Gu et al, 2008;Tao et al, 2019), and reflexes including cough are observed in human volunteers and in animals challenged with aerosolized nicotine (Burch et al, 1989;Hansson et al, 1994;Lee et al, 1985;Lee et al, 2007;McConnell et al, 2017;Soule et al, 2020).…”
Section: Significance Statementmentioning
confidence: 99%